2018
DOI: 10.1213/ane.0000000000003545
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of Endotheliopathy and Bleeding in Thoracic Aortic Dissections: The VIPER-OCTA Randomized Clinical Pilot Trial

Abstract: BACKGROUND:Thoracic aorta dissection is an acute critical condition associated with shock-induced endotheliopathy, coagulopathy, massive bleeding, and significant morbidity and mortality. Our aim was to compare the effect of coagulation support with solvent/detergent-treated pooled plasma (OctaplasLG) versus standard fresh frozen plasma (FFP) on glycocalyx and endothelial injury, bleeding, and transfusion requirements.METHODS:Investigator-initiated, single-center, blinded, randomized clinical pilot trial of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 45 publications
0
40
0
6
Order By: Relevance
“…Nachdem die Gabe von Plasma zur Volumentherapie des schweren hämorrhagischen Schocks verpönt war, wird derzeit als der am besten geeignete Volumenersatz Plasma, insbesondere im präklinischen Kontext, erneut kontrovers diskutiert. Die akute Hypovolämie durch Blutung führt u. a. zu einer Endotheliopathie, die auf der Schädigung der Glykokalyx basiert [9].…”
Section: Therapie Prähospitale Behandlung Massiver Blutungen Von Polyunclassified
See 1 more Smart Citation
“…Nachdem die Gabe von Plasma zur Volumentherapie des schweren hämorrhagischen Schocks verpönt war, wird derzeit als der am besten geeignete Volumenersatz Plasma, insbesondere im präklinischen Kontext, erneut kontrovers diskutiert. Die akute Hypovolämie durch Blutung führt u. a. zu einer Endotheliopathie, die auf der Schädigung der Glykokalyx basiert [9].…”
Section: Therapie Prähospitale Behandlung Massiver Blutungen Von Polyunclassified
“…das Endothel für Zellbotenstoffe und Immunzellen durchgängig [4,8]. Ein entscheidender zusätzlicher Faktor dürfte hierbei der Verlust der Integrität der Glykokalyx sein [9]. An Traumapatienten konnte gezeigt werden, dass ein erhöhter Syndecan-1-Spiegel als Zeichen einer Degradation der Glykokalyx mit einer erhöhten Mortalität vergesellschaftet ist.…”
unclassified
“…Older versions of S/D plasma were associated with hyperfibrinolysis and bleeding; however, changes to the manufacturing process have mitigated the risk of these adverse events . In several studies conducted with the current version of Octaplas, no additional risk of these or other adverse events was identified . No clinically relevant differences in efficacy were identified; however, most of these studies were small and may not have been powered to show significant differences …”
Section: Session 2: Implementation Of Prt For Blood Products In the Umentioning
confidence: 99%
“…During the 20‐year interval, there were seven randomized controlled trials evaluating the safety and efficacy of S/D plasma versus various comparators (see Table ): three in liver transplant/liver disease patients, two in open heart surgery, one in thoracic aortic dissections, and one in healthy volunteers . Two additional reports were excluded: one described a subset of patients included in another trial and one studied a product that is no longer manufactured and was withdrawn from US and Canadian markets in the 2000s .…”
Section: Scientific Reviewmentioning
confidence: 99%
“…Synopsis: Fifteen observational trials and seven RCTs were used to evaluate the safety of S/D plasma. No study reported an increase in AE in S/D plasma compared to conventional plasma and most reported a decrease.…”
Section: Product Efficacymentioning
confidence: 99%